2018
DOI: 10.3390/ijms19041075
|View full text |Cite
|
Sign up to set email alerts
|

The Combinational Use of CRISPR/Cas9 and Targeted Toxin Technology Enables Efficient Isolation of Bi-Allelic Knockout Non-Human Mammalian Clones

Abstract: Recent advances in genome editing systems such as clustered regularly interspaced short palindromic repeats/CRISPR-associated protein-9 nuclease (CRISPR/Cas9) have facilitated genomic modification in mammalian cells. However, most systems employ transient treatment with selective drugs such as puromycin to obtain the desired genome-edited cells, which often allows some untransfected cells to survive and decreases the efficiency of generating genome-edited cells. Here, we developed a novel targeted toxin-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…embryonic stem cells using CRISPR-Cas9 to validate and confirm the role of this protein in these processes. [106][107][108]…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation
“…embryonic stem cells using CRISPR-Cas9 to validate and confirm the role of this protein in these processes. [106][107][108]…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…CRISPR-Cas9 knockout of Tbx1 in murine stem cells (E14-Tg2a) enabled chromatin remodeling studies and transcriptome analyses to understand the pathogenesis of this syndrome [ 105 ]. Similarly, the putative adhesion receptor protein DGCR2, which has shown muscular defects as well as the risk for developing schizophrenia in DiGeorge syndrome, was deleted in mouse TT2 embryonic stem cells using CRISPR-Cas9 to validate and confirm the role of this protein in these processes [ 106 - 108 ].…”
Section: Applications Of Crispr-cas9 For Chdmentioning
confidence: 99%
“…Testis-derived porcine fibroblasts [27] were cultured in Dulbecco's modified Eagle's medium or Ham's F-12 medium (#048-29785; Wako Pure Chemical Industries, Ltd., Osaka, Japan) supplemented with 10% fetal bovine serum (FBS) and 1% antibiotic-antimycotic solution (#A5955; Sigma-Aldrich Co. Ltd., St. Louis, MO, USA) [hereafter referred to as the PF medium] at 37 °C in 5% CO2 atmosphere.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…This query could be resolved by referring to a few previous reports. Watanabe et al [27] employed a paper method [3] for isolating colonies and demonstrated the successful destruction of the DiGeorge syndrome critical region gene 2 (Dgcr2) locus in mouse ESCs after co-transfection with the vectors carrying the Cas9 gene and the gRNA (targeted to Dgcr2), introduction of the gene encoding endo--galactosidase (capable of cleaving the -Gal epitope), and subsequent selection using IB4SAP. Furthermore, the transforming growth factor-β receptor type 1 (TGFβRI) gene was successfully destroyed in porcine adipocyte precursor cells (PAPCs) using similar technology.…”
Section: Name Of Clonesmentioning
confidence: 99%
“…Among currently available genome editing tools, CRISPR/Cas9 is widely used to manipulate GOI in a variety of cells and organisms [74,75,76,77,78,79]. It requires the use of synthetic gRNAs that bind to specific chromosomal DNA sites with Cas9 endonuclease [80,81].…”
Section: Present Status Of Tpgdmentioning
confidence: 99%